The Applications of Health Informatics in Medical Tourism Industry of Iran - Peyman REZAEI-HACHESU; Reza SAFDARI; Marjan GHAZISAEEDI; Taha SAMAD-SOLTANI (Tehran University of Medical Sciences, 2017)
Please provide alternate text for this image to ensure accessibility for users with text-only browsers or assistive devices